Pseudomonas aeruginosa biofilm formation and its resistance to beta-lactam antibiotics - Cynthia Gozali; Conny Riana Tjampakasari (Bahasa Indonesia, 2023)
ABSTRACT Introduction: An opportunistic pathogen, Pseudomonas aeruginosa is a Gram-negative bacteria that causes acute and chronic human infections. By adhering to appropriate surfaces and creating a biofilm matrix, Pseudomonas aeruginosa has a high-resistance structure. Due to biofilm resistance mechanisms, this bacterial biofilm may increase natural antibiotic resistance. Antibiotics have difficulty penetrating the exopolysaccharide matrix that makes up the biofilm structure (Psl, Pe, alginate, and eDNA). Alginate is involved in generating mucus, and Psl and Pel components are implicated in biofilm development and antibiotic resistance. Due to the connection between biofilm production and antibiotic resistance, Pseudomonas aeruginosa involves mechanisms of beta-lactam antibiotic resistance. Objective: On this basis, learning more about the connection between Pseudomonas aeruginosa bacteria's ability to form biofilms and their resistance to beta-lactam antibiotics is essential. Methods: We use literature methods from various literature on the biofilm formation of P. aeruginosa and its resistance to beta-lactam antibiotics, including research papers and studies with no restrictions types of studies included in this article. Discussion: Pseudomonas aeruginosa has intrinsic and adaptive antibiotic resistance mechanisms. Decreased membrane permeability, the production of enzymes resistant to antibiotics, chromosomal changes, and horizontal gene transfer from other bacteria contribute to antimicrobial resistance. Beta-lactam antibiotic resistance mechanisms are known to be developed by Pseudomonas aeruginosa. The resistance characteristics of Pseudomonas aeruginosa may change phenotypically due to biofilm development. This article will be helpful in future research on Pseudomonas aeruginosa therapy and medication.